NO idea how to do this. Can someone please help me? {-x + 3y = -1 x- 2y = 2
Follow Math Help Forum on Facebook and Google+
y=1 x=4
How did you get that?
Originally Posted by SoobadatMath. NO idea how to do this. Can someone please help me? {-x + 3y = -1 x- 2y = 2 add the two equations, term for term ... -x + 3y = -1 x - 2y = 2 ------------ 0 + y = 1 ... note that the x terms cancel now sub 1 in for y in either equation and solve for x.
So then x + 3y = -4 y + x = 0 ???????????????????
Originally Posted by SoobadatMath. So then x + 3y = -4 y + x = 0 ??????????????????? What are you doing ? You were told that y = 1. So replace the y with 1 in one of the equations, then solve for x.
Originally Posted by SoobadatMath. So then x + 3y = -4 y + x = 0 ??????????????????? new system ... x + 3y = -4 y + x = 0 multiply every term in the second equation by -1 ... x + 3y = -4 -x - y = 0 ------------- add 'em up and solve.
x + 3y = -4 [1] y + x = 0 [2] If that's a new system, then from [2]: y = -x So [1]: x - 3x = -4
View Tag Cloud